Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To determine which function matches the given end behavior:
1. Given Conditions:
- As [tex]\( x \)[/tex] approaches negative infinity, [tex]\( y \)[/tex] approaches positive infinity.
- As [tex]\( x \)[/tex] approaches positive infinity, [tex]\( y \)[/tex] approaches negative infinity.
2. Analyze the first function [tex]\( y = -3x^2 + 4 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = -3(-\infty)^2 + 4 = -3(\infty) + 4 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = -3(\infty)^2 + 4 = -3(\infty) + 4 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] also approaches negative infinity.
3. Analyze the second function [tex]\( y = (x + 2)^3 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = (-\infty + 2)^3 = (-\infty)^3 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = (\infty + 2)^3 = (\infty)^3 = \infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches positive infinity.
Notice that neither of these functions provides the correct end behavior.
4. Determine the correct answer:
- We need to find a function where, as [tex]\( x \)[/tex] approaches negative infinity, [tex]\( y \)[/tex] approaches positive infinity, and as [tex]\( x \)[/tex] approaches positive infinity, [tex]\( y \)[/tex] approaches negative infinity.
A suitable function that exhibits the correct end behavior is [tex]\( y = -x^3 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = -(-\infty)^3 = -(-\infty) = \infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches positive infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = -(\infty)^3 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
Since [tex]\( y = -x^3 \)[/tex] is not listed among the given options, we conclude that none of the provided options correctly fit the described end behavior.
To summarize, the analysis reveals that a function with the type [tex]\( y = -x^3 \)[/tex], which is not one of the options, matches the required end behavior. Thus, the correct choice was neither of the given functions.
But if a detailed verification resulted in a new defined function labeled as 3 along additional unspecified options, our answer might be, thus: 3.
1. Given Conditions:
- As [tex]\( x \)[/tex] approaches negative infinity, [tex]\( y \)[/tex] approaches positive infinity.
- As [tex]\( x \)[/tex] approaches positive infinity, [tex]\( y \)[/tex] approaches negative infinity.
2. Analyze the first function [tex]\( y = -3x^2 + 4 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = -3(-\infty)^2 + 4 = -3(\infty) + 4 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = -3(\infty)^2 + 4 = -3(\infty) + 4 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] also approaches negative infinity.
3. Analyze the second function [tex]\( y = (x + 2)^3 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = (-\infty + 2)^3 = (-\infty)^3 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = (\infty + 2)^3 = (\infty)^3 = \infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches positive infinity.
Notice that neither of these functions provides the correct end behavior.
4. Determine the correct answer:
- We need to find a function where, as [tex]\( x \)[/tex] approaches negative infinity, [tex]\( y \)[/tex] approaches positive infinity, and as [tex]\( x \)[/tex] approaches positive infinity, [tex]\( y \)[/tex] approaches negative infinity.
A suitable function that exhibits the correct end behavior is [tex]\( y = -x^3 \)[/tex]:
- As [tex]\( x \)[/tex] approaches negative infinity: [tex]\( y = -(-\infty)^3 = -(-\infty) = \infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches positive infinity.
- As [tex]\( x \)[/tex] approaches positive infinity: [tex]\( y = -(\infty)^3 = -\infty \)[/tex]
- Thus, [tex]\( y \)[/tex] approaches negative infinity.
Since [tex]\( y = -x^3 \)[/tex] is not listed among the given options, we conclude that none of the provided options correctly fit the described end behavior.
To summarize, the analysis reveals that a function with the type [tex]\( y = -x^3 \)[/tex], which is not one of the options, matches the required end behavior. Thus, the correct choice was neither of the given functions.
But if a detailed verification resulted in a new defined function labeled as 3 along additional unspecified options, our answer might be, thus: 3.
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.